2015
DOI: 10.1093/gerona/glv121
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Phenotype and Polyfunctionality Are Associated With Elevated Soluble Inflammatory Markers, Cytomegalovirus Infection, and Functional and Cognitive Decline in Elderly Adults

Abstract: Monocytes are mediators of the inflammatory response and include three subsets: classical, intermediate, and nonclassical. Little is known about the phenotypical and functional age-related changes in monocytes and their association with soluble inflammatory biomarkers, cytomegalovirus infection, and functional and mental decline. We assayed the activation ex vivo and the responsiveness to TLR2 and TLR4 agonists in vitro in the three subsets and assessed the intracellular production of IL1-alpha (α), IL1-beta (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…Monocytes, which are innate immune cells, are known to be mediators of the inflammatory response and comprise at least three different subsets, based on their expression of CD14 (a pattern recognition receptor binding microorganism-derived lipopolysaccharide) and CD16 (a low affinity receptor for the Fc portion of immunoglobulins), namely classical, intermediate and non-classical monocytes. An age-related increase in frequencies of intermediate and nonclassical monocytes has been reported (de Pablo-Bernal et al, 2016;Hearps et al, 2012). Our results from the Berlin Aging Study II confirmed these findings, where we also found an agerelated increase in frequencies of intermediate and non-classical monocytes (unpublished results).…”
Section: Immunosenescence and "Inflammaging"supporting
confidence: 90%
“…Monocytes, which are innate immune cells, are known to be mediators of the inflammatory response and comprise at least three different subsets, based on their expression of CD14 (a pattern recognition receptor binding microorganism-derived lipopolysaccharide) and CD16 (a low affinity receptor for the Fc portion of immunoglobulins), namely classical, intermediate and non-classical monocytes. An age-related increase in frequencies of intermediate and nonclassical monocytes has been reported (de Pablo-Bernal et al, 2016;Hearps et al, 2012). Our results from the Berlin Aging Study II confirmed these findings, where we also found an agerelated increase in frequencies of intermediate and non-classical monocytes (unpublished results).…”
Section: Immunosenescence and "Inflammaging"supporting
confidence: 90%
“…Plasma samples were collected in EDTA-lined tubes, and aliquoted and stored at −20 °C. The levels of high sensitivity C-reactive protein (hsCRP) and β2-microglobulin (β2M), D-dimer, IL-6 and sCD163 were performed as described 22 .…”
Section: Susceptibility and Viral Inhibition Assay Cd4 + T Cells Alomentioning
confidence: 99%
“…A well-controlled CMV infection is likely to have different effects than one that is poorly controlled and, indeed, in previous studies, CMV antibody titers correlated with peak antibody response after influenza vaccination where serostatus did not (den Elzen et al, 2011; Furman et al, 2015; Trzonkowski et al, 2003). CMV antibody titers also correlated with markers of immune activation (de Pablo-Bernal et al, 2015; Trzonkowski et al, 2003). The age of the archived samples in the present study (dating back to 2001) suggested that serostatus could be more reliably measured than antibody titer; however, future research should examine both CMV serostatus and titers.…”
Section: Discussionmentioning
confidence: 88%
“…The cytokine profile of senescent cells is more proinflammatory than non-senescent cells (Effros, 2012; Effros, Dagrarag, Spaulding, & Man, 2005). CMV antibody titers correlate with proinflammatory cytokines in serum, as well as monocyte activation (de Pablo-Bernal et al, 2015; Trzonkowski et al, 2003). Ultimately, enhanced “inflammaging” due to CMV could increase risk for multiple health problems of older adulthood (Ershler & Keller, 2000; Frasca & Blomberg, 2016).…”
Section: Introductionmentioning
confidence: 99%